Proceedings of the International Symposium on Sustainable Energy and Power Engineering 2021 SUSE 2021 - Irina, Akhmetova; Zunino, Pietro; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book comprises the proceedings of the International Symposium on Sustainable Energy and Power Engineering (SUSE) 2021. The contents of this volume focus on recent technological advances in the field of energy efficiency and green buildings, new construction materials and related technology, hydrogen and renewable energy, environmental aspects of the modern power industry, etc. The contents cover latest advances especially in digital transformation of society and economy of the energy sector, turbomachines and combined plants, intelligent energy systems. This volume will prove a valuable resource for those in academia and industry. .
Research of the Combined-cycle Cogeneration Plant$1 (Bs Behavior according to the Temperature Chart -- Pressurized Heat Recovery Steam Generator Design for CCGT with Gas Turbine GT-25PA and Steam Turbine T-100 -- Selection of the Appropriate Intelligence Level of Regulators of Thermal Power Plants Technological Processes.s
Keywords: Renewable energy sources; Electric power production; Sustainable architecture; Renewable Energy; Electrical Power Engineering; Sustainable Architecture/Green Buildings; Renewable energy sources -- Congresses; Electric power systems -- Congresses